2016
DOI: 10.1016/j.aninu.2016.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Progress in the biological function of alpha-enolase

Abstract: Alpha-enolase (ENO1), also known as 2-phospho-D-glycerate hydrolase, is a metalloenzyme that catalyzes the conversion of 2-phosphoglyceric acid to phosphoenolpyruvic acid in the glycolytic pathway. It is a multifunctional glycolytic enzyme involved in cellular stress, bacterial and fungal infections, autoantigen activities, the occurrence and metastasis of cancer, parasitic infections, and the growth, development and reproduction of organisms. This article mainly reviews the basic characteristics and biologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
102
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(108 citation statements)
references
References 56 publications
0
102
1
1
Order By: Relevance
“…Recent studies have demonstrated that glycolytic enzymes such as Enolases play a critical role in glycolysis in cancer cells [21]. ENO1, one of four types of Enolase isozymes, has been detected in almost all mature tissues [22,23]. The functions of ENO1 is now considered to be both a plasminogen receptor, which can promote in ammatory responses in several tumors [24], and a glycolytic enzyme, which participates in catalyzing the penultimate step in glycolysis [23].…”
Section: Read Full Licensementioning
confidence: 99%
“…Recent studies have demonstrated that glycolytic enzymes such as Enolases play a critical role in glycolysis in cancer cells [21]. ENO1, one of four types of Enolase isozymes, has been detected in almost all mature tissues [22,23]. The functions of ENO1 is now considered to be both a plasminogen receptor, which can promote in ammatory responses in several tumors [24], and a glycolytic enzyme, which participates in catalyzing the penultimate step in glycolysis [23].…”
Section: Read Full Licensementioning
confidence: 99%
“…The presence of enolase on the cell surface of the studied fungi was also confirmed by transmission microscopy using the immunogold stain. Figure 4 showed that enolase appears distributed along the cell wall of Ss16345, Ss1099-18, Ss250 and Ss256, which might facilitate its recognition by the host’s immune system, although it also appears, as expected, in the cellular cytoplasm of these species, since its classical function is to catalyze the reversible conversion of 2-phosphoglycerate to phosphoenolpyruvate 22,33 .…”
Section: Resultsmentioning
confidence: 74%
“…Enolase (2-phospho-D-glycerate hydrolase, EC 4.2.1.11) is a metalloenzyme that requires the metal ion magnesium (Mg 2 +) to catalyze the dehydration of 2-phosphoglycerate (2-PG) to phosphoenolpyruvate (PEP), a product that is used to produce energy (ATP) in eukaryotic and prokaryotic cells 21 . In mammals, there are at least 4 subunits of enolase: α-enolase (eno1), expressed in almost all tissues; β-enolase (eno3), predominantly expressed in adult skeletal muscle; γ-enolase (eno2), found in neurons and neuroendocrine tissues 22 ; and eno4, expressed in human and mouse sperm 23 . Enolase has been identified on the cell surface of C. albicans 24 , Plasmodium falciparum 25 , Ascaris suum 26 , Streptococcus sobrinus 27 , S. suis serotipo II 28 , S. iniae 29 , Plasmodium spp 30 and Clonorchis sinensis 31 .…”
Section: Introductionmentioning
confidence: 99%
“…28 The study reported that MYC expression are elevated in TNBC compared with other BC subtypes using a synthetic lethal approach dependent on cyclindependent kinase inhibition, which effectively induced tumor regression in triple-negative tumor xenografts. 33 The presence of glycolytic enzyme enolase (ENO1) and GLS function in glycolysis and glutaminolysis, showed that TNBC had a specific energy metabolism compared with other BC subtypes. 30 It is found that pharmacological inhibition of fatty acid oxidation (FAO) decreased energy metabolism and blocked tumor growth in MYC-driven transgenic TNBC model and MYC-overexpressing TNBC patient-derived xenograft suggesting that FAO inhibitors could be a putative therapeutic strategy for MYC over-expressing TNBC tumors.…”
Section: Discussionmentioning
confidence: 99%